Study On Development Of Independent Rice Mile Unit (IRMU) In Central Lombok District - Wiryono, Budy; Irawan Johari, Harry (Brazilian Journal of Biometrics, 2023)
The strategic role of agriculture is in line with the goals of national economic development, namely: (1) improving the welfare of the indonesian people; (2) accelerating economic growth, reducing poverty; (3) providing employment; (4) maintaining the balance of natural resources and the environment. The research entitled “Study on the Development of Independent Rice Mile Unit (IRMU)in Central Lombok District” aims to determinate the feasibility of building an Independent Rice Mile Unit (IRMU) based on five aspects of plants feasibility, including demographic characteristics, aspect of the management of grain and rice (including among them grain and rice distribution), socio-economic factors environmental elements, and accessibility aspects in Central Lombok regency. The method used in this research is a descriptive survey approach. The study was conducted in March –July 2019. Data sources used in this study were primary data, namely informants, and secondary data, namelydocuments, journals, etc. The data collection techniques used were observation, interviews, documentation, literature, and questionnaires. The data analysis technique used is descriptive analysis. This study indicates that the placement of IRMU locations in the Central Lombok Regency is very suitable because it is supported by all aspects studied.